The flipped approach to higher education - Sahin, Muhammed; Kurban, Caroline Fell
Prelims -- The socio-economic and socio-technical nature of todays world and how this impacts the education sector -- Flipped learning: a transformative approach designed to meet the needs of todays knowledge economies and societies -- From current practice to future practice: making the decision to flip -- Organizational design and transformation -- Flipped learning theory, policies, and practices -- Flipped leadership: transparency, vision, accountability, and resources -- Supporting flipped learning: digital pedagogy, training, and resources -- Engaging students in a flipped language learning environment: stories from the English language preparatory program -- Flipping language, literature, and digital literacies: stories from the school of foreign languages -- How the faculty of engineering is developing its flipped approach -- Creating the flipped educators of the future: leading by example in the faculty of education -- Differentiating flipped learning approaches for the diverse needs of the faculty of Economics, administrative, and Social sciences -- Flipped learning in Legal education: a personal experience -- How it emerged that the approach to arts, design, and architecture already contains a flip -- Flipped learning through the eyes of the students: tales and anecdotes -- Cultural aspects inherent in flipped learning -- Milestones for success -- Acknowledgements -- References -- Index
From the worlds first completely flipped institution, the authors address the socio-economic and socio-technical nature of today's world and how this impacts what is needed from the education sector, outlining how and why they adopted Flipped Learning as the transformative approach required to meet these needs, and definitively describe the organizational design process needed to establish a Flipped institution, from physical and geographical infrastructure, to human and intellectual capital. Included in this book are chapters in which administrators, pedagogical and technical support staff, instructors and students share their experiences and lessons learned in the first year and how the Flipped approach has impacted their education experience. These experiences are then used to develop performance improvement initiatives for leadership, institutional commitment, the infrastructure, and instructor and student support and development
Includes bibliographical references
Keywords: bisacsh; Education / Administration / Higher; Higher & further education, tertiary education; Blended learning; Teaching / Methodology / History; Education / Study and teaching (Higher); Educational innovations